Relationship Between Low Birth Weight and Pregnant Women's HB Results - Yayun Gunibala; Rosyidah Alfitri; Rani Safitri (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Low Birth Weight (LBW) is one of the main risk factors that contribute to neonatal morbidity and mortality. One of the factors that can affect the incidence of LBW is the hemoglobin (Hb) level of pregnant women. Pregnant women with low Hb levels (anemia) have a higher risk of giving birth to low birth weight babies. This study was conducted to analyze the relationship between Hb levels of pregnant women and the incidence of LBW at the Motolohu Health Center, Rancangan District, Pohuwato Regency, Gorontalo Province. This study aims to determine the relationship between Hb levels of pregnant women and the incidence of LBW at Motolohu Health Center. This study used a quantitative method with a cross-sectional study design. The sample in this study amounted to 30 respondents selected using purposive sampling techniques. Data were collected through medical records and structured interviews. Data analysis was performed using the Chi-Square statistical test with a significance level of 0.05. The results of the analysis showed that there was a significant relationship between maternal Hb levels and the incidence of LBW, with a p-value of 0.000 (p ≤ 0.05). This indicates that pregnant women with low Hb levels are at higher risk of giving birth to low birth weight babies compared to mothers with normal Hb levels. There is a significant relationship between maternal Hb levels and the incidence of LBW. Low Hb levels in pregnant women can increase the risk of delivery with low birth weight, so more attention is needed to nutritional intake and iron supplementation during pregnancy.